Molecular detection and characterization of Babesia bovis, Babesia bigemina, Theileria species and Anaplasma marginale isolated from cattle in Kenya. Issue 1 (December 2015) - Adjou Moumouni, Paul; Aboge, Gabriel; Terkawi, Mohamad; Masatani, Tatsunori; Cao, Shinuo; Kamyingkird, Ketsarin; Jirapattharasate, Charoonluk; Zhou, Mo; Wang, Guanbo; Liu, Mingming; Iguchi, Aiko; Vudriko, Patrick; et al.
Abstract Background Infections withBabesia bovis, Babesia bigemina, Theileria species andAnaplasma marginale are endemic in Kenya yet there is a lack of adequate information on their genotypes. This study established the genetic diversities of the above tick-borne hemoparasites infecting cattle in Kenya. Methods Nested PCR and sequencing were used to determine the prevalence and genetic diversity of the above parasites in 192 cattle blood samples collected from Ngong and Machakos farms.B. bovis spherical body protein 4, B. bigemina rhoptry-associated protein 1a, A. marginale major surface protein 5, Theileria spp. 18S rRNA, T. parva p104 andT. orientalis major piroplasm surface protein were used as the marker genes. Results B. bovis, B. bigemina, T. parva, T. velifera, T. taurotragi, T. mutans andA. marginale were prevalent in both farms, whereasT. ovis, Theileria sp. (buffalo) andT. orientalis were found only in Ngong farm. Co-infections were observed in more than 50 % of positive samples in both farms.Babesia parasites andA. marginale sequences were highly conserved whileT. parva andT. orientalis were polymorphic. Cattle-derivedT. parva was detected in Machakos farm. However, cattle and buffalo–derivedTheileria were detected in Ngong farm suggesting interactions between cattle and wild buffaloes. Generally, the pathogens detected in Kenya were genetically related to the other African isolates but different from the isolates in other continents. Conclusions The current findings reaffirm the endemicity and co-infection of cattle with tick-borne hemoparasites, and the role of wildlife in pathogens transmission and population genetics in Kenya.